Nilai- Nilai Yang Terkandung Dalam Tradisi Rewang (Kojo Samo) Pada Masyarakat Desa Delik Kecamatan Pelalawan Kabupaten Pelalawan Provinsi Riau - Disnia Salwa Ramadhani; Yahyar Erawati (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
This study aims to determine the values contained in the Rewang (kojo samo) tradition in the community of Delik Village, Pelalawan District, Pelalawan Regency, Riau Province. This research uses the theory of Uu Hamidy (2014: 49). The method used is descriptive qualitative approach. Data collection through observation, interviews and documentation. The subjects in this study amounted to 4 people consisting of 1 Batin Dolik (Delik Village tribal leader), 1 Delik Village customary leader, 2 Rewang members (kojo samo). The results of this study conclude that the Rewang Tradition (kojo samo) is a hereditary tradition that is preserved and considered important by the Delik Village Community because of cooperation and can help ease the burden in a celebration event activity, namely marriage. Rewang (kojo samo) tradition contains educational value, religious value, social value and tradition value. The value of education in the rewang tradition is to receive teachings that the community or the younger generation does not know in cooking. The religious value of the rewang tradition is eating together and praying (thanksgiving) for the smooth running of the wedding tomorrow. The social value of the rewang tradition is the existence of mutual help, and cooperation between the community and other communities. The value of tradition in the rewang tradition (kojo samo) is that it has become a community habit that the elders used to do until now.